Experimental Birthmarks: New Cases of an Asian Practice - Tucker, Jim B; Keil, H. H. Jürgen (Journal of Scientific Exploration, 2013)
<span style="font-family: "Times New Roman"; font-size: 12pt; mso-bidi-font-size: 10.0pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Experimental birthmarks involve a practice in several countries in Asia in which the body of a dying or recently deceased person is marked with a substance, most often soot, in the belief that when the individual is reborn, the baby will bear a birthmark corresponding to the mark. This is usually done with the expectation that the rebirth will occur in the same family as the deceased individual. A field study was undertaken in Thailand and Myanmar (Burma) to examine such cases. Eighteen cases were found in which a baby was born with a birthmark that corresponded to a marking made on the body of a deceased person; in six of these, the child also made statements that the family believed were related to the life of the deceased individual. Possible etiologies for these cases are explored. Keywords: Birthmarks—experimental birthmarks—reincarnation